Succeeding as a teacher effective management for positive student achievement - Morgan, Nancy Battista; Alvarez, Ana; Magna Systems (Barrington, Ill. : Magna Systems, Inc., 2006)
This DVD program and accompanying workshop manual will give beginning teachers the background and skills to become successful teachers. It will show how to plan and prepare meaning instruction; use instructional strategies that help al students; put into effect proven classroom management skills; and communicate and grow as a professional.
Part 1. Planning instruction -- Part 2. Instruction for all students -- Part 3. Managing the learning environment -- Part 4. Communication and professional growth.
Title from disc label
Narrator, Ana Alvarez
DVD
Keywords: Teacher effectiveness; Classroom management; Teacher-student relationships